Novel LRPPRC compound heterozygous mutation in a child with early-onset Leigh syndrome French-Canadian type: case report of an Italian patient - Ettore Piro; Gregorio Serra; Vincenzo Antona; Mario Giuffrè; Elisa Giorgio; Fabio Sirchia; Ingrid Anne Mandy Schierz; Alfredo Brusco; Giovanni Corsello (BMC, 2020)
Abstract Background Mitochondrial diseases, also known as oxidative phosphorylation (OXPHOS) disorders, with a prevalence rate of 1:5000, are the most frequent inherited metabolic diseases. Leigh Syndrome French Canadian type (LSFC), is caused by mutations in the nuclear gene (2p16) leucine-rich pentatricopeptide repeat-containing (LRPPRC). It is an autosomal recessive neurogenetic OXPHOS disorder, phenotypically distinct from other types of Leigh syndrome, with a carrier frequency up to 1:23 and an incidence of 1:2063 in the Saguenay-Lac-St Jean region of Quebec. Recently, LSFC has also been reported outside the French-Canadian population. Patient presentation We report a male Italian (Sicilian) child, born preterm at 28 + 6/7 weeks gestation, carrying a novel LRPPRC compound heterozygous mutation, with facial dysmorphisms, neonatal hypotonia, non-epileptic paroxysmal motor phenomena, and absent sucking-swallowing-breathing coordination requiring, at 4.5 months, a percutaneous endoscopic gastrostomy tube placement. At 5 months brain Magnetic Resonance Imaging showed diffuse cortical atrophy, hypoplasia of corpus callosum, cerebellar vermis hypoplasia, and unfolded hippocampi. Both auditory and visual evoked potentials were pathological. In the following months Video EEG confirmed the persistence of sporadic non epileptic motor phenomena. No episode of metabolic decompensation, acidosis or ketosis, frequently observed in LSFC has been reported. Actually, aged 14 months corrected age for prematurity, the child shows a severe global developmental delay. Metabolic investigations and array Comparative Genomic Hybridization (aCGH) results were normal. Whole-exome sequencing (WES) found a compound heterozygous mutation in the LRPPRC gene, c.1921-7A > G and c.2056A > G (p.Ile686Val), splicing-site and missense variants, inherited from the mother and the father, respectively. Conclusions We first characterized the clinical and molecular features of a novel LRPPRC variant in a male Sicilian child with early onset encephalopathy and psychomotor impairment. Our patient showed a phenotype characterized by a severe neurodevelopmental delay and absence of metabolic decompensation attributable to a probable residual enzymatic activity. LRPPRC is a rare cause of metabolic encephalopathy outside of Québec. Our patient adds to and broaden the spectrum of LSFC phenotypes. WES analysis is a pivotal genetic test and should be performed in infants and children with hypotonia and developmental delay in whom metabolic investigations and aCGH are normal.